Somatosensory evoked potentials and outcome in perinatal asphyxia. Issue 4 (April 1992) - Gibson, N A; Graham, M; Levene, M I
Abstract : Somatosensory evoked potentials (SEP) can be measured in the term newborn infant and given an index of function in the areas of the brain most likely to be damaged in perinatal asphyxia. We studied the median nerve SEP in 30 asphyxiated term infants over the course of their encephalopathy and until discharge from the neonatal unit. Three types of response were noted: normal waveform, abnormal waveform, or absence of cortical response. Follow up of the survivors was undertaken at a mean age of 12 months by means of a Griffiths' assessment and neurological examination. Nine infants died of their asphyxial illness and one of spinal muscular atrophy. Of the 20 survivors, three have cerebral palsy, four have minor abnormalities, and 13 are neurodevelopmentally normal. There was a close correlation between outcome and SEP. All 13 infants with normal outcome had normal SEP by 4 days of age, whereas those with abnormal or absent responses beyond 4 days had abnormalities at follow up.